How Do Actinyls Interact with Hyperphosphorylated Yolk Protein Phosvitin?. Issue 53 (1st August 2019) - Kumar, Sumit; Creff, Gaëlle; Hennig, Christoph; Rossberg, André; Steudtner, Robin; Raff, Johannes; Vidaud, Claude; Oberhaensli, François R.; Bottein, Marie‐Yasmine Dechraoui; Den Auwer, Christophe
Abstract: The development of the nuclear industry has raised multiple questions about its impact on the biotope and humans. Proteins are key biomolecules in cell machinery and essential in deciphering toxicological processes. Phosvitin was chosen as a relevant model for phosphorylated proteins because of its important role as an iron, calcium, and magnesium storage protein in egg yolk. A multitechnique spectroscopic investigation was performed to reveal the coordination geometry of two oxocations of the actinide family (actinyl U VI, Np V ) in speciation with phosvitin. IR spectroscopy revealed phosphoryl groups as the main functional groups interacting with U VI . This was confirmed through laser luminescence spectroscopy (U) and UV/Vis absorption spectroscopy (Np). For U VI, X‐ray absorption spectroscopy at the LIII edge revealed a small contribution of bidentate binding present, along with predominantly monodentate binding of phosphoryl groups; for Np V, uniquely bidentate binding was revealed. As a perspective to this work, X‐ray absorption spectroscopy speciation of U VI and Np V in the extracted yolk of living eggs of the dogfish Scyliorhinus canicula was determined; this corroborated the binding of phosphorous together with a reduction of the actinyl moiety. Such data are essential to pinpoint the mechanisms of heavy metals (actinyls) accumulation and toxicity in oviparous organisms, and therefore, contribute to a shift from descriptive approaches to predictive toxicology. Abstract : Tracing species : Phosvitin is a model phosphorylated protein with an important role as an iron, calcium, and magnesium storage protein in egg yolk. A multitechnique spectroscopic investigation was performed to reveal the coordination mechanism of two oxocations of the actinide family (U VI, Np V ) in speciation with phosvitin (see figure).